Traditional medicinal plants used for rheumatoid arthritis and immune system disorders treatment in the Casablanca-Settat region, Morocco: An ethnopharmacological study - Zineb Sekkout; Amal EL Hamsas EL Youbi; Omaima Boudaia; Saadia Janani; Driss Radallah; Najat EL Amrani (Elsevier, 2024)
Rheumatoid arthritis, classified as an immune system disorder, stands as a prevalent condition that presents considerable challenges to healthcare systems worldwide. This study was delving into the realm of traditional medicine to explore the use of medicinal plants for the treatment of rheumatoid arthritis and immune system disorders in the Casablanca-Settat region of Morocco. With a focus on ethnopharmacological insights, a comprehensive survey was conducted involving 372 participants, including herbalists and patients, to document the local knowledge and practices associated with these conditions. The findings revealed a noteworthy reliance on traditional medicinal knowledge, with a prominent role played by females across different age groups. A diverse spectrum of 88 plant species hailing from 45 distinct families was identified, where in the Myrtaceae, Oleaceae, and Zingibneraceae families garnered prominence as the most endorsed choices. Noteworthy among these, Zingiber officinale and Curcuma longa emerged as highly favored species, boasting robust anti-inflammatory and immunomodulatory attributes. The study also offers insight regarding preferences concerning administration methods, highlighting the salience of oral consumption and infusion as the predominant modes of preparation. Nevertheless, the observed variability in dosage utilization underscores the traditional therapeutic paradigmsintricacies. Geographic disparities were discernible as well, with certain species displaying a region-specific usage pattern, further enriching the understanding of local herbal practices. Moreover, the study identified endemic species such as Olea europaea, Teucrium polium, Argania spinosa, and Withania adpressa contributing to the safeguarding of the region's indigenous botanical heritage. In conclusion, this study contributes to a deeper understanding of the traditional management of RA and immune system disorders in the Casablanca-Settat region. The documented plant species, practices, and preferences offer valuable insights into potential sources of anti-inflammatory and immunomodulatory agents.